URGENSI KEBIJAKAN HUKUM ASIMILASI DAN HAK INTEGRASI NARAPIDANA TERKAIT PENANGANAN WABAH COVID-19 DI INDONESIA - Yohana Trisha Gloria, (2021)
This study aims to determine whether the urgency of the assimilation policy of prisoners during the covid period, to guarantee the certainty of no repetition of criminal acts and to find out whether the procedure requirements of the assimilation policy are relevant. This study uses a juridical normative legal research method with a qualitative approach. The results of the study show that the legal policy mechanism for assimilation and integration of prisoners has been running in accordance with the procedures and requirements stipulated by Ministerial Decree (Kepmen) Number M.HH-19.PK.01.04.04 of 2020. However, in providing assurance of certainty that there will be no repetition of criminal acts must pay more attention to the aspect of giving maximum punishment to prisoners who repeat criminal acts to trigger other inmates, the goal is that judges no longer need to consider the relief factor for assimilated prisoners who return to acting and there is a need for a legal umbrella for steps to anticipate prisoners' actions in the midst of a pandemic COVID-19. The lack of supervision of prisoners is another reason for more attention. And the procedures for the assimilation and integration policy requirements of prisoners and children during the Covid-19 period are not yet relevant to be implemented in Indonesia, it is better if in issuing a regulation it must be adjusted to developments and legal needs in society. Keywords: covid-19, assimilation, policy urgency